Accessibility and Utilisation of Open Educational Resources in Distance Learning Centres in Nigeria - Ayotunde Atanda Falade; Felicia Afolajuwonlo Ogunsina; Mutiu Babatunde Ibrahim (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
Distance learning has become increasingly important since the COVID-19 pandemic, with educators and institutions turning to open educational resources (OER) to facilitate learning. The study aimed to determine the access of distance learners to open educational resources (OER) for learning; also to examine their utilisation in Oyo State, Nigeria. Employing a descriptive survey research design, data were collected through a Google Form-based online questionnaire from 500 open educational students in three distance learning centres. A total of 381 valid responses were analysed; hypotheses were tested at a significance level of 0.05%, using SPSS. Descriptive statistics were employed to address the research questions. From the findings, it was discovered that students can access the essential devices and OER either via their centre's website or using the free Wi-Fi provided by the centre, with 52.9 % not accessing them and 47.1 % accessing them at least once a week. The utilisation of OER was limited, with some resources rarely or never used by students (always used = 34.4%, rarely used = 32.1%, and never used = 33.5%) among others. The study concluded that distance learners had access to and utilised OER; but some missed out on a valuable and cost-effective resource. Recommendations included improving students' access, encouraging the use of available OER, among many others